Digitising Mersing: a web based biodiversity analysis tool for the East Coast of Johor - Shamsir, Mohd S.; Al-Hadi, Muhammad; Nik Wan, Nik Ahmad Firdaus (2008)
Biodiversity informatics is a currently developing bioinformatics field that contributes to the management of the biodiversity and ecosystem by providing decision making cues to researchers, environmental managers and policymakers. It brings together ecologist, environmentalist and computer scientists to solve real-world conservation challenges while developing the underlying ecological, bioinformatics, and information sciences. However, biodiversity information are currently presented in text databases located in dispersed locations even within the same research institution. The data itself are usually difficult or even inaccessible, flat file formatted and with existing geospatial information in numbered coordinates that is almost meaningless in first instance. Availability of an easy Web based intuitive interface will facilitate and accelerate analysis of biodiversity data. Hence, this motivated us to develop a web based biodiversity and ecosystem informatics database suited for the numerous scattered ecological and biodiversity data typically found in Malaysian research community. The paper presents an online biodiversity database system integrated with GIS with a centralized enterprise repository. Interactive visualization provides an effective way of presenting large amounts of complex information to a wide audience, especially those with no experience of GIS or mapping, as it provides the user with visual cues that are more intuitive than those of a conventional map. It is a scalable database that provides variable and adaptable feature modification for its users. It is also designed to incorporate different layers of knowledge to allow selective viewing to protect sensitive indigenous biodiversity data. The use of spatial information will enable researcher to analyze ecological trends and behavior. The database is also accessible via the web for easy data population and curation.